STRATEGI PEMERINTAH DESA DALAM MENJAGA KESTABILAN EKONOMI MASYARAKAT DESA DI MASA PANDEMI (Studi kasus di Desa Wolaang Kec. Langowan Timur Kab. Minahasa - TICOALU, SHANIA; RURU, JOORIE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2022)
In this increasingly developing era, a nation is required to be able to design sustainable development strategies in advancing its nation. This development can be in the form of physical development or other resources, community empowerment as one of the methods or methods that can be used in the grand framework of national development. The purpose of this study was to determine Community Empowerment through the Immanuel Farmer Group Program in Raringis Village, West Langowan District, Minahasa Regency. The theory used in this study is the theory of Community Empowerment from Sumodiningrat (2007) which contains three stages of empowerment, namely the stage of awareness and behavior formation, the stage of transformation of work abilities, and the stage of increasing intellectual abilities. This study uses descriptive qualitative research, namely to obtain more complete, more in-depth, credible and meaningful data by conducting interviews with 8 informants and also by collecting documents related to community empowerment so that the objectives of the research will be achieved. The results of this study describe community empowerment through the Immanuel farmer group program in Raringis Village, West Langowan District, Minahasa Regency, it has been going quite well in terms of the application of the three indicators of the empowerment stage. Keywords : Empowerment, Program, Farmer Group